Ion-doped Brushite Cements for Bone Regeneration. (15th March 2021) - Hurle, K.; Oliveira, J.M.; Reis, R.L.; Pina, S.; Goetz-Neunhoeffer, F.
Abstract: Decades of research in orthopaedics has culminated in the quest for formidable yet resorbable biomaterials using bioactive materials. Brushite cements most salient features embrace high biocompatibility, bioresorbability, osteoconductivity, self-setting characteristics, handling, and injectability properties. Such type of materials is also effectively applied as drug delivery systems. However, brushite cements possess limited mechanical strength and fast setting times. By means of incorporating bioactive ions, which are incredibly promising in directing cell fate when incorporated within biomaterials, it can yield biomaterials with superior mechanical properties. Therefore, it is a key to develop fine-tuned regenerative medicine therapeutics. A comprehensive overview of the current accomplishments of ion-doped brushite cements for bone tissue repair and regeneration is provided herein. The role of ionic substitution on the cements physicochemical properties, such as structural, setting time, hydration products, injectability, mechanical behaviour and ion release is discussed. Cell-material interactions, osteogenesis, angiogenesis, and antibacterial activity of the ion-doped cements, as well as its potential use as drug delivery carriers are also presented. Statement of significance: Ion-doped brushite cements have unbolted a new era in orthopaedics with high clinical interest to restore bone defects and facilitate the healing process, owing its outstanding bioresorbability and osteoconductive/osteoinductive features. Ion incorporation expands their application by increasing the osteogenic and neovascularization potential of the materials, as well as their mechanical performance. Recent accomplishments of brushite cements incorporating bioactive ions are overviewed. Focus was placed on the role of ions on the physicochemical and biological properties of the biomaterials, namely their structure, setting time, injectability and handling, mechanical behaviour, ion release and in vivo osteogenesis, angiogenesis and vascularization. Antibacterial activity of the cements and their potential use for delivery of drugs are also highlighted herein. Graphical Abstract: Image, graphical abstract